Advancing Financial Inclusion Through Fintech to Drive the Development of A Digital Society - Supartoyo, Yesi Hendriani (Proceedings International Conference on Education Innovation and Social Science, 2022)
It is vital for Indonesia to accelerate the adoption of FinTech to democratize access to financial services. While Indonesia has huge market potential for FinTech, current and potential players have to be aware of the fundamental problems that have been hindering the growth of the sector. There are a number of roadblocks that FinTech players should take into consideration; they revolve around the lack of financial literacy and inclusion. FinTech innovations are enabling access to financial services through mobile devices for many unbanked in the world. Though FinTech innovations are touted as game changers in deepening financial inclusion, their wide acceptance and use still remain limited. Provided a strong financial literacy among the population, Indonesia will be able to achieve full financial inclusion, which can be accelerated with the adoption of FinTech. Financial inclusion is a key factor of social inclusion, particularly effective in combating poverty and income inequality by unlocking blocked advancement opportunities. FinTech is seen as a key enabler of financial inclusion; and mobile financial services, as the type of FinTech with the greatest potential to bring the unbanked into the formal financial system. The FinTech sector needs to prioritize financial literation for all populations of Indonesia to encourage growth in numerous sectors. Supartoyo (2017) on her paper said the financial sector can affect regional economic growth and play an important role to the economic growth of a region. Further implementation of FinTech into society needs to be as accessible as possible.